The Added Value of Molecular Testing in Small Pancreatic Cysts - Toll, Adam D; Kowalski, Thomas; Loren, David; Bibbo, Marluce (JOP. Journal of the Pancreas, 2010)
Context Recent studies have shown high amplitude K-ras gene mutation and allelic imbalances are predictive of malignancy in pancreatic cysts. Objective Our purpose is to determine the added benefit of molecular testing in diagnosing small pancreatic cysts. Design Retrospective, single-institution study. Patients Patients with pancreatic cysts (less than, or equal to, 3 cm) who presented for EUS evaluation. Intervention EUS-guided pancreatic cyst aspiration cytology, carcinoembryonic antigen (CEA) level determination, and detailed DNA analysis including K-ras gene mutation and allelic imbalance. Main outcome measurements Ability of cyst fluid DNA analysis to render a diagnosis compared with cytology and CEA level determination. Results Diagnostic agreement was seen in 55.6% (35/63) of cases. In 10 cases (15.9%), there was disagreement between cytology and molecular. Molecular testing provided a diagnosis in 20 cases (31.7%) when either cytology was unsatisfactory, or CEA not elevated (less than 192 ng/mL). Elevated CEA levels were seen in 16 cases (25.4%), each diagnosed as a mucinous lesion with molecular analysis. Conclusions Molecular analysis of pancreatic cyst fluid adds diagnostic value in scant specimens when cytology may be unsatisfactory and CEA unreliable. Image: Proposed management algorithm for pancreatic cystic neoplasms.